2019
DOI: 10.1002/adfm.201902503
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule‐Doped Organic Crystals with Long‐Persistent Luminescence

Abstract: Traditional long-persistent luminescence (LPL) materials, which are based on inorganic systems containing rare elements and with preparation temperatures of at least 1000 °C, exhibit afterglow times of more than 10 h and can be tuned for different applications. However, the development of this field is hindered due to the large thermal energy consumption and the need for nonrenewable resources. Thus, the development of a "green" design and preparation of LPL materials is of some importance. A doped-crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 27 publications
0
68
0
Order By: Relevance
“…[30][31][32][33] Supramolecular interactions such as inclusion complexation and hydrogen bonding have also been reported to suppress the molecular vibrations of the triplet excited state of the luminescent component to increase F P of room-temperature phosphorescence and afterglow materials. [34][35][36][37][38][39][40] Besides molecular design, aggregation state control and supramolecular assembly, [41][42][43][44][45][46][47][48] two-component design strategies developed by us and other research groups, [49][50][51][52][53][54] where asecond component is employed to control the excited state properties of luminescent component (i.e., the first component), have been shown to enhance the room-temperature phosphorescence and afterglow efficiency.For example,inthe dopant-matrix system, the rigid microenvironment provided by the matrix molecules can inhibit the nonradiative deactivation of the triplet excited states of the dopant molecules, [55,56] and the deuteration of the dopant molecules can further inhibit the vibration of the triplet excited states, leading to the formation of efficient room-temperature afterglow materials. [57] In the co-crystal system, F P as high as 55 %has been achieved through the cooperation of internal and external HAE, whereas t P was reduced to approximately 10 ms. [22] In the donor-acceptor system, the excitation light can cause charge separation, while the charge recombination was strongly suppressed in solid medium, giving rising to organic long persistent luminescence (OLPL) up to hours.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Supramolecular interactions such as inclusion complexation and hydrogen bonding have also been reported to suppress the molecular vibrations of the triplet excited state of the luminescent component to increase F P of room-temperature phosphorescence and afterglow materials. [34][35][36][37][38][39][40] Besides molecular design, aggregation state control and supramolecular assembly, [41][42][43][44][45][46][47][48] two-component design strategies developed by us and other research groups, [49][50][51][52][53][54] where asecond component is employed to control the excited state properties of luminescent component (i.e., the first component), have been shown to enhance the room-temperature phosphorescence and afterglow efficiency.For example,inthe dopant-matrix system, the rigid microenvironment provided by the matrix molecules can inhibit the nonradiative deactivation of the triplet excited states of the dopant molecules, [55,56] and the deuteration of the dopant molecules can further inhibit the vibration of the triplet excited states, leading to the formation of efficient room-temperature afterglow materials. [57] In the co-crystal system, F P as high as 55 %has been achieved through the cooperation of internal and external HAE, whereas t P was reduced to approximately 10 ms. [22] In the donor-acceptor system, the excitation light can cause charge separation, while the charge recombination was strongly suppressed in solid medium, giving rising to organic long persistent luminescence (OLPL) up to hours.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported a new type of metal-organic frameworks (MOFs) with long-lasting afterglow which showed highly tunable afterglow phosphorescence colors upon pyridine solution treatment. This finding supplies a group of MOFs-based persistent luminescence nanophosphors with high performance [150][151][152][153][154]. Up to now, the afterglow MOFs have not been used in biomedical fields in vivo due to the relatively short emission wavelength and the undesirable diameter.…”
Section: New Organic and Polymeric Plnps With Long Afterglow For In Vmentioning
confidence: 72%
“…Molecular organic materials with long‐persistent luminescence at room temperature have potential applications in anticounterfeiting, information storage, data encryption, and bioimaging, and have thus attracted considerable interest in the past decade . Several organic RTP materials with ultralong lifetime have been reported . Huang and An et al.…”
Section: Figurementioning
confidence: 99%